Synthesis and Application of Bifunctional Reactive Dyes Based on 3-(4-Aminophenyl)- 5-benzylidene-2-substituted phenyl-3,5-dihydro-imidazol-4-one - N. Wadia, Devang; M. Patel, Pravin (Asian Journal of Chemistry, 2010)
A series of nine novel heterocyclic based monoazo bifunctional reactive dyes were synthesized using various substituted imidazol-4-one. Heterobifunctional reactive dyes provide great opportunity for efficient dye fiber reaction due to the mixed double-anchors such as sulphatoethylsulphone and monochlorotriazinyl reactive groups, which may cover a wide range of application temperatures. Prepared heterobifunctional reactive dyes were applied to wool fibers using various parameters. The optimized exhaustion (% E) and fixation (% F) were determined. Analysis of dye solutions being adjusted to different pH conditions was carried out to verify the structure of dye moieties. The synthesized dyes were characterized using standard spectroscopic methods and then dyeing performance on wool fabric was assessed. Wash and light fastness properties of prepared dyes showed promising results.